1987
DOI: 10.1111/j.1600-051x.1987.tb01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periodontal therapy on specific antibody responses to suspected periodontopathogens*

Abstract: The effects of clinically successful periodontal therapy were studied in juvenile periodontitis (JP) and rapidly progressive periodontitis (RP) patients and compared with periodontally healthy subjects (HS). Serum samples were obtained in 35 HS prior to the study and in 12 of these subjects 3-4 years later. Serum samples were obtained from 50 JP patients initially, 9 subjects immediately following surgical therapy and 29 of these subjects 3-4 years later. RP patients provided 46 initial serum samples, 9 follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…Taken together, and in accordance to earlier reports (Vincent et al 1987, Taubman et al 1992), our findings suggest that periodontitis patients and subjects non‐susceptible to periodontitis elicit serum IgG responses to periodontal microbiota of clearly distinct intensities, and that these differences do persist after therapy. The observed discriminative potential of serum antibody responses and their relative stability over time suggest that serology to periodontal bacteria is a useful complement in the armamentarium of diagnostic tools for periodontal diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, and in accordance to earlier reports (Vincent et al 1987, Taubman et al 1992), our findings suggest that periodontitis patients and subjects non‐susceptible to periodontitis elicit serum IgG responses to periodontal microbiota of clearly distinct intensities, and that these differences do persist after therapy. The observed discriminative potential of serum antibody responses and their relative stability over time suggest that serology to periodontal bacteria is a useful complement in the armamentarium of diagnostic tools for periodontal diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Genco et al (52) and Ebersole et al (47) have shown significantly increased levels of antibody towards A. actinomycetemcomitans in localized early-onset periodontitis and generalized early-onset periodontitis patients. Other studies have confirmed these findings (Table 4), with Vincent et al (175,176) reporting that localized juvenile periodontitis subjects have a much higher antibody titers towards A. actinomycetemcomitans than adult periodontitis or generalized early-onset periodontitis subjects. They also found that a much greater percentage of these localized early-onset periodontitis patients were A. actinomycetemcomitans seropositive than in comparison to generalized early-onset periodontitis.…”
Section: Humoral Response To Periodontal Organisms As An Indicator Ofmentioning
confidence: 68%
“…Higher numbers of localized early‐onset periodontitis and generalized early‐onset periodontitis subjects are seropositive towards P. gingivalis than healthy controls and have much higher levels of antibody (175, 176). In this study, generalized early‐onset periodontitis patients had much higher antibody titers to P. gingivalis than localized early‐onset periodontitis subjects.…”
Section: Humoral Response To Periodontal Organisms As An Indicator Ofmentioning
confidence: 99%
“…actinomycetemcomitans antigens in sera of patients with aggressive periodontitis (localized juvenile periodontitis) that was absent from normal subjects (Genco et al, 1980). Many, although not all, patients with periodontitis produce a humoral immune response to periodontal disease-associated bacteria and their antigens during the course of a periodontal infection ( Mouton et al, 1981;Ebersole et al, 1982a,b;Taubman et al, 1982a;Tew et al, 1985;Ebersole et al, 1986;Vincent et al, 1987;Ishikawa et al, 1988;Murayama et al, 1988;Zambon et al, 1988a,b;Ogawa et al, 1990;Chen et al, 1991b;Whitney et al, 1992;Ling et al, 1993). The role such antibodies may play in the onset and progression of the disease is not totally clear.…”
Section: Humoral Immune Response In Patients With Periodontitismentioning
confidence: 96%
“…The role such antibodies may play in the onset and progression of the disease is not totally clear. Periodontal therapy appears to have a marked effect on the humoral immune response to antigens of periodontopathic bacteria Vincent et al, 1987;Murayama et al, 1988). Therapeutic intervention by scaling and root planing or by surgery significantly enhances serum antibody levels and avidities to antigens of P. gingivalis and induces seroconversion in seronegative patients Chen et al, 1991a;Sjostrom et al, 1994).…”
Section: Humoral Immune Response In Patients With Periodontitismentioning
confidence: 97%